Secured online voting system using face recognition (International Journal of Advanced Research in Science, Management and Technology, 2017)
Now a day, voting for any social issue is important for modern democratic societies. Manual voting system is implemented for election from many years in our country. We have proposed online voting system and we are using face recognition to secure the system. System captures image and makes their shares and if the shares are matched then and then only the user can proceed for voting Otherwise, the user is considered as invalid user or voter.
Keywords: Voting, Democratic Societies, Election, face recognition